Cysteines and Disulfide-Bridged Macrocyclic Mimics of Teixobactin Analogues and Their Antibacterial Activity Evaluation against Methicillin-Resistant Staphylococcus Aureus (MRSA) - Ruba Malkawi; Abhishek Iyer; Anish Parmar; Daniel G. Lloyd; Eunice Tze Leng Goh; Edward J. Taylor; Sarir Sarmad; Annemieke Madder; Rajamani Lakshminarayanan; Ishwar Singh (MDPI AG, 2018)
Teixobactin is a highly potent cyclic depsipeptide which kills a broad range of multi-drug resistant, Gram-positive bacteria, such as Methicillin-resistant Staphylococcus aureus (MRSA) without detectable resistance. In this work, we describe the design and rapid synthesis of novel teixobactin analogues containing two cysteine moieties, and the corresponding disulfide-bridged cyclic analogues. These analogues differ from previously reported analogues, such as an Arg10-teixobactin, in terms of their macrocyclic ring size, and feature a disulfide bridge instead of an ester linkage. The new teixobactin analogues were screened against Methicillin-resistant Staphylococcus aureus and Methicillin-sensitive Staphylococcus aureus. Interestingly, one teixobactin analogue containing all l-amino acid building blocks showed antibacterial activity against MRSA for the first time. Our data indicates that macrocyclisation of teixobactin analogues with disulfide bridging is important for improved antibacterial activity. In our work, we have demonstrated the unprecedented use of a disulfide bridge in constructing the macrocyclic ring of teixobactin analogues.